La vieillesse d’Amon-Rê à Karnak - Biston-Moulin, Sébastien (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
This article reconsiders an obscure passage from the White Chapel of Senusret I at Karnak. The newly proposed reading is compared to a related text from the Akh-menu of Thutmosis III at Karnak. These two inscriptions refer, five hundred years apart, to the two major phases of the refoundation of the temple of Amun-Ra at Karnak, through the shared metaphor of the god’s aging and rejuvenation.